Comorbid Diseases and Outcomes of Critically Ill COVID-19 Patients Admitted to an Indonesian Intensive Care Unit from May to October 2021 - Katrin Wilentina Siahaan; I Ketut Agus Somia; I Made Susila Utama; Ni Made Dewi Dian; Anak Agung Ayu Yuli Gayatri; Cokorda Agung Wahyu Purnamasidhi; Ketut Tuti Parwati Merati (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2). The spread of COVID-19 has become a worldwide health threat, with 583,038,110 cases and a death toll of 6,416,023. This study attempted to determine the relationship of age, sex, and comorbid diseases with the outcomes of critically ill COVID-19 patients at Prof. Dr. IGNG Ngoerah Central General Hospital, Denpasar, Indonesia.